The Role of Argument-Based Science Inquiry Learning Model to Improve Scientific Argumentation Ability - Rohayati, Rohayati; Syihabuddin, Syihabuddin; Anshori, Dadang; Sastromiharjo, Andoyo (Jurnal Pendidikan Progresif, 2022)
The Role of The Argument Based Science Inquiry (Absi) Learning Model To Improve Scientific Argumentation Ability. Objectives: The purpose of this study was to determine the role of the argument-based science inquiry (ABSI) learning model in improving scientific argumentation skills. Methods: The quasi-experimental method used in this study was a one group pretest posttest design. The population in this study were high school students in the city of Bandung with a sample of two classes selected by cluster random sampling with a total of 100 students. Findings: The results of the study confirm that the ABSI learning model has a very significant effect on students' scientific argumentation skills. The improvement can be seen in the depth, organization, and accuracy scientific argumentation.  Conclusion: Students' argumentation skills increase because they are trained to organize thoughts completely, scientifically, and systematically. Keywords: argument-Based Science Inquiry (ABSI) learning model, Scientific argumentation ability, critical thinking ability.DOI: http://dx.doi.org/10.23960/jpp.v12.i3.202223